(untitled) (Annals of Medical Research, 2021)
Aim: Myopericarditis/Perimyocarditis is an inflammation in the heart muscle. There is an increase in cardiac biochemical markers with echocardiographic (ECHO) and/or electrocardiographic (ECG) changes in patients. We aimed to investigate the demographic, clinical, laboratory and imaging features and follow-up results of patients diagnosed with acute myopericarditis in our clinic. Materials and Methods: In this study, demographic and laboratory data and physical examination findings of 15 pediatric patients diagnosed with myopericarditis between December 2017-September 2020 were retrospectively recorded. Results: Five (33.3%) of the patients were girls, 10 (66.6%) were boys. The first presentation complaint was chest pain in 11 (73.3%) patients, palpitations in two (13.3%) patients, respiratory distress, abdominal pain and vomiting in two (13.3%) patients. Troponin values were increased in all cases. N-terminal prohormone brain natriuretic peptide (NT-ProBNP) level was>100 pg/ml in seven patients. In treatment, nine patients received ibuprofen, and three patients received inotrope and anticongestive therapy support as well as intravenous immunoglobulin (IVIG). In the follow-up, heart functions normalized within four months in all cases. Conclusion: Myopericarditis should be considered especially in adolescent boys who present with complaints such as chest pain, palpitations, respiratory distress, and cardiac enzyme elevation and ECG changes. Although the prognosis is good in most of myopericarditis cases, the risk of morbidity may be high in patients with high initial cardiac enzyme values, delayed cardiac enzyme return to normal, and systolic dysfunction on ECHO, so long-term follow-up of these patients should be done by pediatric cardiologists.